1986
DOI: 10.1007/bf01913556
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behaviour of rigid polyurethane foams

Abstract: By means of a combined thermal analysis technique,, the thermal behaviour of rigid polyurethane foams containing additive antipyrenes was studied. The presence of phosphorus-and phosphorus/chlorine-containing antipyrenes based on phosphate and phosphonate and a combination of them led to decreases in the rates of heat and weight loss during heating. More steps of decomposition were formed and the interval of decomposition was widened and shifted to higher temperatures. Some thermal characteristics make it poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…The latter decomposes in two stages in the interval from 230 to 670 ~ while for compositions I and II 3 or 4 steps of decomposition are observed and the temperature intervals widen and shift mainly to higher temperatures: 820 ~ in air, and 850 ~ in nitrogen atmosphere, A similar tendency was found for polyurethane elastomers (PUE) modified with P and P/Cl-containing antipyrenes [9], and also for RPUF containing additive antipyrenes with the same active elements, P and CI [1]. The latter decomposes in two stages in the interval from 230 to 670 ~ while for compositions I and II 3 or 4 steps of decomposition are observed and the temperature intervals widen and shift mainly to higher temperatures: 820 ~ in air, and 850 ~ in nitrogen atmosphere, A similar tendency was found for polyurethane elastomers (PUE) modified with P and P/Cl-containing antipyrenes [9], and also for RPUF containing additive antipyrenes with the same active elements, P and CI [1].…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…The latter decomposes in two stages in the interval from 230 to 670 ~ while for compositions I and II 3 or 4 steps of decomposition are observed and the temperature intervals widen and shift mainly to higher temperatures: 820 ~ in air, and 850 ~ in nitrogen atmosphere, A similar tendency was found for polyurethane elastomers (PUE) modified with P and P/Cl-containing antipyrenes [9], and also for RPUF containing additive antipyrenes with the same active elements, P and CI [1]. The latter decomposes in two stages in the interval from 230 to 670 ~ while for compositions I and II 3 or 4 steps of decomposition are observed and the temperature intervals widen and shift mainly to higher temperatures: 820 ~ in air, and 850 ~ in nitrogen atmosphere, A similar tendency was found for polyurethane elastomers (PUE) modified with P and P/Cl-containing antipyrenes [9], and also for RPUF containing additive antipyrenes with the same active elements, P and CI [1].…”
Section: Resultsmentioning
confidence: 62%
“…This requires the development of laboratory methods which are minimum time-, labour-and material-consuming and can provide .the maximum insight into the mechanism of the inhibitory effect of antipyrenes [1][2][3][4].Additive antipyrenes are not always efficient enough. It is shown that dynamic thermal analysis can register the changes resulting in the mechanisms and kinetics of the thermal decompositions of the investigated polyurethanes from comparatively low concentrations and differences in the concentrations and from differences in the chemical compositions and structures of the antipyrenes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are some major deficiencies of rigid PU foam (PUF), which restricts their further compatibility and applications including inadequate mechanical strength, high flammability and thermal stability. In recent years, flame‐retardant rigid PU has attracted considerable attention owing to the increasing demand for rigid PU foam in the field of energy‐efficient building materials . The low flammability, may also particularly be useful for cabin interiors, where foams may be used in conjunction with other materials, such as leathers, that generally exhibit higher heat and smoke release values .…”
Section: Introductionmentioning
confidence: 99%